Chi-Square Analysis of the Percentage of the Bottom 40% Expenditure Group Aged 0–17 Years with Birth Certificate Ownership in Indonesia - Herman, Ayuthia Ramadhani (Reflection: Education and Pedagogical Insights, 2025)
This study investigates the relationship between household expenditure levels and birth certificate ownership among children aged 0–17 years in Indonesia. Using secondary data from Badan Pusat Statistik (BPS) for the period 2015–2017, the research applies the Chi-Square test of independence (contingency table analysis) to determine whether children from the bottom 40% expenditure group are less likely to possess birth certificates compared to other groups. The results show that the Chi-Square value (χ² = 0.019174) at a 5% significance level indicates no statistically significant association between household expenditure group and birth certificate ownership. This finding suggests that efforts by the Indonesian government to improve civil registration may have contributed to reducing inequality across income groups. Despite this, regional and micro-level disparities may still persist. The study highlights the importance of continuous policy interventions, awareness programs, and integrated registration services to ensure universal birth certificate coverage for all children in Indonesia.